2011
DOI: 10.1095/biolreprod.110.088526
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Dual-Specificity Phosphatase 1 (DUSP1) by Pulsatile Gonadotropin-Releasing Hormone Stimulation: Role for Gonadotropin Subunit Expression in Mouse Pituitary LbetaT2 Cells1

Abstract: In pituitary gonadotrophs, GnRH induces expression of the mitogen-activated protein kinases (MAPK3/1) dephosphorylating enzyme, dual-specificity phosphatase 1 (DUSP1). Here we examined DUSP1 expression levels following pulsatile GnRH stimulation of the LbetaT2 gonadotroph cells. DUSP1 expression was increased more prominently following high-frequency (every 30 min) GnRH pulse stimulation (7.02- ± 1.47-fold) than low-frequency (every 120 min) GnRH pulses (2.68- ± 0.09-fold). With high-frequency GnRH pulses, DUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Subsequently, the feedback activity of MKP1, which inactivates MAPK via dephosphorylation, was found to modulate GnRH-induced ERK activation and gonadotropin response to GnRH (34,35). Finally, MKP1 expression was shown to be predominant under high GnRH frequency compared with low GnRH frequency (36). The relationship and relative importance of these various loci which have been implicated in frequency decoding remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the feedback activity of MKP1, which inactivates MAPK via dephosphorylation, was found to modulate GnRH-induced ERK activation and gonadotropin response to GnRH (34,35). Finally, MKP1 expression was shown to be predominant under high GnRH frequency compared with low GnRH frequency (36). The relationship and relative importance of these various loci which have been implicated in frequency decoding remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with data demonstrating that mutation of the site which governs ERK MKP binding affects ERK2-GFP translocation kinetics in response to continuous, but not pulsatile, GnRH (Armstrong et al, 2010), the findings from this group argue against a major role for MKP's in mediating the decoding of the pulsatile GnRH response. Lastly, studies conducted in LβT2 cells demonstrated a significant increase in dual-specificity kinase 1 (DUSP1) after fast GnRH pulse frequencies compared to control and slow frequency stimulated samples (Purwana et al, 2011). In these LβT2 cells, overexpression of MAP3K1 induced both Fshb and Lhb subunit promoter activities, which was inhibited by cotransfection with DUSP1 expression vectors (Purwana et al, 2011).…”
Section: Signaling Pathways Activated By Pulsatile Gnrhmentioning
confidence: 99%
“…MAPs are a family of protein phosphatases that inactivate ERK by dephosphorylation of threonine and/or tyrosine residues [44]. MKP expression was predominantly increased following high-rather than low-frequency GnRH pulses [45]. Because MKP induced by high-frequency GnRH pulses dephosphorylates ERK, which is activated by the initial GnRH pulse, ERK phosphorylation induced by a single GnRH pulse during high-frequency GnRH pulse stimulation would return to the basal level more rapidly.…”
Section: Gonadotropin Secretion From Pituitary Gonadotrophsmentioning
confidence: 99%